1997
DOI: 10.1093/carcin/18.6.1149
|View full text |Cite
|
Sign up to set email alerts
|

Altered gap junctional intercellular communication in neoplastic rat esophageal epithelial cells

Abstract: Gap junctional intercellular communication (GJIC) is reduced in many neoplastic cells, but few data exist for esophageal neoplasms. GJIC was examined by fluorescent dye microinjection in two nontumorigenic and two highly tumorigenic rat esophageal epithelial cell lines. All lines expressed high levels of dye coupling in homologous cell culture. In cocultures of nontumorigenic and tumorigenic cells, however, only one of six cell combinations displayed significant heterologous GJIC. Northern, Western, and immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…Previous connexin transfection/ transduction and connexin antisense studies [13][14][15][16][17][18][19][20][21][22][23], however, provided direct evidence to the contrary. In addition, studies from several groups indicated that neoplastic cells can express functional gap junctions among themselves (homologous GJIC) but be incapable of forming gap junctions with normal cells (heterologous GJIC) [37][38][39][40]. As Loewenstein [7] first noted, neoplastic cells may manifest defective GJIC in several ways including the lack of gap junctions or the formation of gap junctions with reduced channel permeability, the inability to form gap junctions with normal cells (lack of heterologous GJIC), and the inability to respond to junctional signal molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Previous connexin transfection/ transduction and connexin antisense studies [13][14][15][16][17][18][19][20][21][22][23], however, provided direct evidence to the contrary. In addition, studies from several groups indicated that neoplastic cells can express functional gap junctions among themselves (homologous GJIC) but be incapable of forming gap junctions with normal cells (heterologous GJIC) [37][38][39][40]. As Loewenstein [7] first noted, neoplastic cells may manifest defective GJIC in several ways including the lack of gap junctions or the formation of gap junctions with reduced channel permeability, the inability to form gap junctions with normal cells (lack of heterologous GJIC), and the inability to respond to junctional signal molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The glycocalyx encompasses five different classes of adhesion molecules (immunoglobulins, integrins, cadherins, selectins, and cell adhesion molecules) that directly connect it to the ECM [2]. Furthermore, the glycocalyx of the plasma membrane directly influences the ability of cells to form gap junction channels [115], reviewed in [116]. In this manner, the glycocalyx itself influences how information is filtered and forwarded.…”
Section: (2) Cell-cell Communication In Microenvironment and Carcinogmentioning
confidence: 99%
“…2 cx43 is a tumor-suppressor gene. 1,3,4 Expression of cx43 is reduced in human mammary carcinoma, 5,6 prostate cancer, 7,8 human glioblastoma, 4,9 skin squamous-cell carcinoma, 10 lung-cancer cells, [11][12][13] esophageal cancer cells 14,15 and human mesothelioma. 16 Transfection of cx43 restored several "normal" phenotypes to neoplastic cells, including rat C6 glioma, 17,18 human mammary carcinoma, 19 human glioblastoma, 4 transformed dog kidney epithelial cells, 3 rhabdomyosarcoma cells 20 and lung-cancer cells.…”
mentioning
confidence: 99%